Novalis : German Poet-European Thinker-Christian Mystic - Hiebel, Friedrich, 1903-1989 (University of North Carolina studies in the Germanic languages and literatures ;, 2020)
Originally published in 1954, Hiebel's Novalis was the first critical evaluation in English of the life and works of Novalis (1772-1801), the German Romantic poet of the Blue Flower, since Thomas Carlyle's essay in 1829. This book presents not only a fully rounded picture of the man, the philosopher and scientist, the writer of beautiful fairy tales, the mystic poet of Christianity, but also a thoughtful commentary on one of the most influential and fruitful periods in German intellectual life. Hiebel combines the exactness required of the scholar with the creative writer's intuitive appreciation of a great poet's works.